Therapeutic effects of curcumin-loaded cockle shell-derived CaCO₃ nanoparticles on lead-induced toxicity damage in a rat model - Muhammad, Mailafiya Maryam (2019)
Lead toxicity is an alarming global threat that intoxicates multiple organs particularly the brain. Prolong lead exposure resulted into approximately 494,550 deaths and contributed around 10% of intellectual disability globally. Recently the use of curcumin (Cur) as an alternative therapy for the treatment of heavy metal-induced toxicity is attracting nucleus attentions. Despite its remarkable pharmacological activities, it remains clinically constrained due to its poor bioavailability when orally administered. Currently cockle shell-derived calcium carbonate nanoparticle (CSCaCO3NP) is gaining more acceptance in nanomedicine as a nanocarrier to various therapeutics. Hence, this study was designed to evaluate the therapeutic effect of curcumin-loaded CSCaCO3NP on lead-induced toxicity in rats. Synthesis of CSCaCO3NP as a potential drug carrier for curcumin delivery was conducted using a simple top-down method. The physicochemical properties of CSCaCO3NP and Cur- CSCaCO3NP were characterized using standard techniques. Cur-CSCaCO3NP in vitro kinetic release mechanism was evaluated using the dialysis bag membrane method. Cytotoxicity assessment was carried out using WST’s assay. For in vivo study, thirtysix male adults Sprague-Dawley rats were randomly assigned into five groups. All groups contained six rats each apart from group A which contained 12 rats. All rats apart from the rats in group A (control) were orally administered a flat dose of 50 mg/kg of lead for four weeks. Six rats from the control and group B were euthanized for toxicity confirmatory tests at week four. Oral administration of curcumin (100 mg/kg) for group C and Cur-CSCaCO3NP (50 and 100 mg/kg) for group D and E respectively, commenced at week 5 and ended in week 8. Motor function test was performed using horizontal bar method and all rats were euthanize at the 8th week of the experiment. Further, biochemical, histological and histochemical analysis were performed. A spherical shaped CSCaCO3NP with a surface area of 14.48±0.1 m2/g, mean diameter of 21.38±2.7 nm and a zeta potential of -18.5 mV was synthesized which has a high loading capacity. The FT-IR and XRD revealed fewer observable changes on the peaks after conjugation. In vitro kinetic release profile demonstrated slow and steady release at pH 1.2 compared to the rapid release at pH 7.4. WST’s assay showed no apparent toxicity and high biocompatibility on normal cells. The findings from the in vivo assessments revealed significant (p <0.05) impaired motor functions, biochemical, haematological, histochemical and histological alterations in lead-induced rats. Although, the rats treated with free curcumin showed some ameliorative effects, Cur-CSCaCO3NP treatment demonstrated an enhanced therapeutic effect through significant (p < 0.05) improvements on motor coordination, haematological parameters, histochemical and histological features, increased SOD activities and decreased MDA levels, when compared to free curcumin treatment. The findings of the current study holds great prospects for Cur-CSCaCO3NP as a novel approach for effective oral treatment of lead-induced neurodegenerations as well as hepato-renal impairments.